The Role of Four-Dimensional Automatic Right Ventricular Quantification Technology to Determine RV Function and Hemodynamics in Patients With Pulmonary Hypertension Compared With Right Heart Catheterization - Wu, Weichun; Liu, Bingyang; Huang, Min; Hsi, David H.; Niu, LiLi; Tian, Yue; Lin, Jingru; Wang, Jiangtao; Yang, Shuai; Lu, Hongquan; Xiong, Changming; Zhu, Zhenhui; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Four-dimensional automatic right ventricular quantification technology (4D auto-RVQ) is a new method that can simultaneously measure right ventricular (RV) structure and strain. The role of 4D auto-RVQ in determining RV function and hemodynamics is not clear. The role of 4D auto-RVQ in determining RV function and hemodynamics is not clear. We assessed the 4D auto-RVQ to measure right heart structure, function, and hemodynamics in patients with pulmonary hypertension (PHTN) correlated with right heart catheterization (RHC). Methods: We enrolled a prospective cohort of 103 patients with PHTN and 25 healthy controls between September 2017 and December 2018. All patients with PHTN underwent echocardiography and RHC. Patients were included if they underwent two-dimensional (2D) and 4D auto-RVQ echocardiographic sequences on the same day as RHC. We analyzed RV functional indices using 2D and 4D auto-RVQ analyses. We divided patients with PHTN into three groups according to echocardiographic image quality as follows: high (n = 24), average (n = 48), and poor (n = 4). Hemodynamic parameters were measured using RHC, including mean right atrial pressure, mean pulmonary arterial pressure, RV cardiac index (RV-CI), and pulmonary vascular resistance. Results: There were significant differences in most 2D and 4D auto-RVQ parameters between patients with PHTN and healthy controls. Interobserver variability showed significant agreement with 4D auto-RVQ for most measurements except for 4D end-diastolic volume. Indices measured by auto 4D-RVQ in the high-quality image group had a good correlation with RHC but not in the average and poor-quality image group. Mid-RV diameter showed the best predictive power for the right RV-CI (area under the curve [AUC] 0.935, 95% confidence interval [CI] 0.714–0.997, P < 0.001). RV end-systolic volume >121.50 ml had a 71.43% sensitivity and a 100% specificity to predict right RV-CI (AUC 0.890, 95% CI 0.654–0.986, P < 0.001). Conclusions: 4D auto-RVQ may be used to estimate RV function and some hemodynamic changes compared with RHC in PHTN patients with high image quality. Furthermore, a large sample of the study is needed to evaluate RV function by 4D auto-RVQ in PHTN patients with average image quality.